PENGARUH PROBLEM BASED LEARNING DAN THINK PAIR SHARE BERBASIS BLENDED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA - sugiyanti Sugiyanti; Murtono Murtono; Sri Surachmi W (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The COVID-19 pandemic has changed the learning system in Indonesia from face-to-face learning to distance. Such changes in the learning system need to be addressed with the use of learning models that are in accordance with the current distance learning system. Blended learning is a learning approach that combines face-to-face and online learning as an alternative to this changing learning system. This study aimed to determine the effect of the model on problem based learning (PBL) and think pair share (TPS) based on blended learning on students' mathematics learning outcomes and knowing the differences in learning outcomes between-based PBL and TPS models model blended learning. This study utilized quantitative research by comparing two learning models to students' mathematics learning outcomes. The research sample was from sixth grade students of SD N Mojo 1 and SD N Trengguli 3 in Kabupaten Demak. The results showed that the PBL model based on blended learning had an effect of 80.5% on students' learning outcomes, the TPS model based on blended learning had an effect of 71.9% on students' learning outcomes, and both models had no difference on the students' learning outcomes. This showed that the blended learning approach in the PBL and TPS models significantly influenced students' mathematics learning outcomes.